2016
DOI: 10.1515/manment-2015-0011
|View full text |Cite
|
Sign up to set email alerts
|

The role of Public Service Motivation and Organizational Culture for Organizational Commitment

Abstract: SummaryThe aim of the our paper is to discuss the relationships between organizational culture, Public Service Motivation (PSM) and organizational commitment (OC). On the basis of literature review we formulated hypotheses presenting potential relationships between mentioned constructs. We propose that there is a mutual influence between PSM and organizational culture and that organizational culture moderates the influence of Public Service Motivation on organizational commitment. Due to the presence of variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 48 publications
(16 reference statements)
0
15
0
3
Order By: Relevance
“…Dwivedi et al (2014), Manetje and Martins (2009) believe on the existence of a positive relationship between the culture and commitment in the organizations. Noticeable scholars in the field of organizational culture and commitment (Ahmed Shah et al, 2012;Austen & Zacny, 2015;Lok & Crawford 2004;Silverthorne, 2004) confirmed that there is a positive relationship between organizational culture and commitment, and found that employees' performance enhancement and commitment have been affected positively by organizational culture (Austen & Zacny, 2015;Lok & Crawford, 2004). It has been also recognized that the strength of the organizational culture increases the organizational commitment of the employees (Ahmed Shah et al, 2012;Austen & Zacny, 2015;Dwivedi et al, 2014).…”
Section: Organization Culture and Commitmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Dwivedi et al (2014), Manetje and Martins (2009) believe on the existence of a positive relationship between the culture and commitment in the organizations. Noticeable scholars in the field of organizational culture and commitment (Ahmed Shah et al, 2012;Austen & Zacny, 2015;Lok & Crawford 2004;Silverthorne, 2004) confirmed that there is a positive relationship between organizational culture and commitment, and found that employees' performance enhancement and commitment have been affected positively by organizational culture (Austen & Zacny, 2015;Lok & Crawford, 2004). It has been also recognized that the strength of the organizational culture increases the organizational commitment of the employees (Ahmed Shah et al, 2012;Austen & Zacny, 2015;Dwivedi et al, 2014).…”
Section: Organization Culture and Commitmentmentioning
confidence: 99%
“…Noticeable scholars in the field of organizational culture and commitment (Ahmed Shah et al, 2012;Austen & Zacny, 2015;Lok & Crawford 2004;Silverthorne, 2004) confirmed that there is a positive relationship between organizational culture and commitment, and found that employees' performance enhancement and commitment have been affected positively by organizational culture (Austen & Zacny, 2015;Lok & Crawford, 2004). It has been also recognized that the strength of the organizational culture increases the organizational commitment of the employees (Ahmed Shah et al, 2012;Austen & Zacny, 2015;Dwivedi et al, 2014). Moreover, the Literature shows that number of researchers argued that factors of innovative and supportive cultures have strong positive relationship with organizational commitment and job satisfaction, whereas factor of bureaucratic cultures have a negative relationship with the organizational commitment (Li, 2004;Lok & Crawford, 2004;Manetje & Martins, 2009;Abdul Rashid et al, 2003;Silverthorne 2004).…”
Section: Organization Culture and Commitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In Austen and Zacny's (2015) study, organizational culture, involving organizational values, physical environment, and an organization's overall climate, is a moderator that adjusts the relationship between the APS and CPV dimensions of PSM, and organizational commitment. Note that the mechanism is different from that of the mediation relationships through the perception of P-O fit, because here we attribute the insignificant direct result to the moderation through facing the organizational culture and being affected unconsciously.…”
Section: Resultsmentioning
confidence: 99%
“…problems, policies and politics [21]. There is a need to focus on the relative roles of each department with respect to the commitment and motivation, funding, administration, organization and service delivery [22]. The POSHAN Mission is highly ambitious in aiming for a targeted reduction of key malnutrition indicators by 2022, and needs to meticulously address the emerging crisis of declines in IYCF indicators.…”
Section: Concluding Commentsmentioning
confidence: 99%